Britain in balance - Manser, W. A. P. (London : Longman [for] the Institute of Economic Affairs, 1971)
This book sets out to do two things. Firstly, to provide an explanation for laymen of the nature of the post-war balance of payments problem; and secondly, to advance the author's own particular diagnosis and cure.
Includes index.
Includes bibliographical references: p. 206-210
usc 09/05/2018
Loans
Keywords: Balance of payments; Economic history; Economic policy; Great Britain